RESPON SISWA TERHADAP SANKSI TINDAKAN PELANGGARAN TATA TERTIB DI SMP DWI SEJAHTERA PEKANBARU - Harahap, Muda; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in junior high Dwi Sejahterah Pekanbaru. The school is located in Street Dirgantara No. 4, Sidomulyo Timur, city of Pekanbaru. This research aims to find out how the students responses and response of the elderly against sanctions acts violating the code of conduct of the school. The theory is a theory of social aberration, response theory, social control theory. The technique of sampling, the census is used in this study there are 23 students and parents of students with 23 total number of 46 people respondents. Data analysis was performed by means of a quantitative descriptive analysis with data collection in the form of observation, interview, questionnaire, documentation. From the results of the research field noted that the response from the students more dominant not agree to sanctions that have to pay the costs. On the respondent's parents based on influence factors work against sanctions acts violating the school's code of conduct namely 12 persons or 52.2% disagreed with the sanctions bring 5-10 paving block, 15 people or 65.2% disagreed with the sanctions bring 1 zak cement, 13 people or 56.5% disagree with sanctions brought law enforcement school, 12 people or 52.2% disagreed with the sanctions bring pots and flower, 13 people or 56.5% disagreed with the sanctions bring 1 tin of paint. Then the factors affecting job not agree parents students against sanctions given the school. Â